2008
DOI: 10.1097/gme.0b013e3180ca7cfa
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous and hemodynamic responses during hot flashes in symptomatic postmenopausal women

Abstract: Objective-The aim of this study was to test the hypothesis that the postmenopausal hot flash is accompanied by rapid decreases in arterial blood pressure and increases in cutaneous vascular conductance (CVC), as evaluated by continuous measurements of these variables in symptomatic women.Design-Twelve healthy, normotensive, postmenopausal women rested in a temperature-controlled laboratory (26°C) for approximately 90 minutes. The onset of a hot flash was objectively identified as a transient and pronounced ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 28 publications
(32 reference statements)
4
41
1
Order By: Relevance
“…Although many studies have reported associations between VMS and adverse cardiovascular risk profile [15,16], others either failed to show such associations [18][19][20][21] or point towards a favorable link between VMS and cardiovascular parameters [22][23][24]. Although the relation between VMS and cardiovascular risk is an area of active inquiry, interpretation of the often conflicting findings remains a challenge.…”
Section: Introductionmentioning
confidence: 91%
“…Although many studies have reported associations between VMS and adverse cardiovascular risk profile [15,16], others either failed to show such associations [18][19][20][21] or point towards a favorable link between VMS and cardiovascular parameters [22][23][24]. Although the relation between VMS and cardiovascular risk is an area of active inquiry, interpretation of the often conflicting findings remains a challenge.…”
Section: Introductionmentioning
confidence: 91%
“…Blood pressure was, however, unchanged indicating that the rise in blood flow to the hand is not a result of a change in systemic arterial pressure, but most likely reflects cutaneous vasodilatation. The increase in skin blood flow during a hot flush episode was recently confirmed with another study [26]. The pattern of change in blood flow through the arm is similar to that seen in response to indirect heating of the body [27], suggesting that the flush may reflect inappropriate activation of the mechanisms for heat loss.…”
mentioning
confidence: 58%
“…Therefore, although blood pressure was found to be either unchanged [25], or dropping when measured during a hot flush episode [26,31], the mean blood pressure level in women reporting hot flushes was higher than in those who do not flush [40].…”
mentioning
confidence: 63%
See 2 more Smart Citations